The Effect of Financial Performance, Dividend Policy on Company Value with Corporate Social Responsibility (CSR) as A Moderating Variable: A Case Study of Manufacturing Companies on the Indonesia Stock Exchange - Resty Kusumawati (Privietlab, 2022)
This study restructures and synthesizes an empirical study on financial performance, dividend policy, corporate social responsibility (CSR), and firm value in Indonesian manufacturing firms listed on the Indonesia Stock Exchange. The original study was driven by the assumption that firm value is shaped not only by profitability and dividend distribution but also by how companies manage liquidity, leverage, and social responsibility in a competitive market. Using secondary data from annual reports and the Indonesian Capital Market Directory for 2007–2011, the study selected 10 manufacturing firms through purposive sampling and produced 50 firm-year observation. Firm value was proxied by Tobin’s Q; financial performance was represented by liquidity, leverage, and profitability ratios; dividend policy was measured by the dividend payout ratio; and CSR disclosure was treated as a moderating variable based on economic, environmental, and social disclosure items. The analysis combined descriptive statistics, classical assumption tests, simple regression, and moderated regression analyses. The findings show that profitability has a positive and significant effect on firm value, and dividend policy also contributes positively to firm value. In contrast, liquidity and leverage do not show significant direct effects in the simple models. CSR does not generally strengthen the relationship between financial performance and firm value, nor does it strengthen the relationship between dividend policy and firm value, although it significantly moderates the leverage–firm value relationship. Overall, the study suggests that investors in the sampled firms responded more strongly to earnings capacity and dividend signals than to CSR disclosure alone.